2017
DOI: 10.3892/mmr.2017.8163
|View full text |Cite
|
Sign up to set email alerts
|

Exploiting novel valve interstitial cell lines to study calcific aortic valve disease

Abstract: Calcific aortic valve disease (CAVD) involves progressive valve leaflet thickening and severe calcification, impairing leaflet motion. The in vitro calcification of primary rat, human, porcine and bovine aortic valve interstitial cells (VICs) is commonly employed to investigate CAVD mechanisms. However, to date, no published studies have utilised cell lines to investigate this process. The present study has therefore generated and evaluated the calcification potential of immortalized cell lines derived from sh… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
10
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 11 publications
(10 citation statements)
references
References 46 publications
0
10
0
Order By: Relevance
“…In line with this, ENCODE data on SCREEN ( https://screen.wenglab.org ) predict that the homologous positions of NEBL 1 and 4 in the human genome are located in cis-regulatory elements (Table 25 in S1 Text ) [ 46 ]. We next used electrophoretic mobility shift assays (EMSA) to investigate potential protein binding to NEBL 1-, 2-, 3- and 4 in-vitro , using nuclear cell extracts from three different cell lines: i) RAVIC (a model for heart valve interstitial cell biology [ 47 ]); ii) H9C2 (differentiated into cardiomyocytes); and iii) MDCK (derived from dog kidney cells and used to finetune the protocol using probe and protein that both originate from dog). For NEBL 3, we documented no clear binding for either allele in any of the cell lines tested (Fig 10 in S1 Text ).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…In line with this, ENCODE data on SCREEN ( https://screen.wenglab.org ) predict that the homologous positions of NEBL 1 and 4 in the human genome are located in cis-regulatory elements (Table 25 in S1 Text ) [ 46 ]. We next used electrophoretic mobility shift assays (EMSA) to investigate potential protein binding to NEBL 1-, 2-, 3- and 4 in-vitro , using nuclear cell extracts from three different cell lines: i) RAVIC (a model for heart valve interstitial cell biology [ 47 ]); ii) H9C2 (differentiated into cardiomyocytes); and iii) MDCK (derived from dog kidney cells and used to finetune the protocol using probe and protein that both originate from dog). For NEBL 3, we documented no clear binding for either allele in any of the cell lines tested (Fig 10 in S1 Text ).…”
Section: Resultsmentioning
confidence: 99%
“…Protein binding to all oligos was assayed in nuclear extracts from three different cell types; i) the MDCK cell line is derived from dog (Cocker spaniel) kidney tubule epithelia and was used as a representative of a non-cardiac derived cell line that allowed us to test binding in a setting where both protein and probe sequence originate from dog; ii) In absence of immortalized cell lines derived from mitral valve, we used RAVIC cells as a model for heart valve interstitial cell biology. RAVIC cells derive from rat (Sprague Dawley rats) aortic valvular interstitial cells [ 47 ]. Similar to the mitral valve, the aortic valve is located in the left side of the heart.…”
Section: Methodsmentioning
confidence: 99%
“…It is known that increasing levels of calcium and phosphate, within the physiological range, induce calcification of valvular interstitial cells in vitro [ 12 ]. Serum is a metastable solution with respect to calcium phosphate precipitation.…”
Section: Discussionmentioning
confidence: 99%
“…First, the size of VIC population within rat valves is very small, and therefore many animals are needed in order to generate sufficient cell numbers for extensive in vitro studies. However, it is possible to overcome this limitation by undertaking preliminary studies in immortalized valve interstitial cell lines, as recently reported by us 18 , and subsequently employing primary cultures to verify and extend these findings.…”
Section: Discussionmentioning
confidence: 99%